Uneven landscapes inhabited by middle Miocene mammals from La Pava and Collón Cura formations in North Patagonia - Alejandro G. Kramarz; Eduardo S. Bellosi; Mariano Bond; Analía M. Forasiepi; Mercedes Fernández; Juan Carlos Fernicola; Guillermo Aguirrezabala; Daniella Teixeira de Rezende (Swiss Journal of Palaeontology)
Abstract The Collón Cura Formation (CCF) bears a diverse assemblage of middle Miocene terrestrial mammals (the Colloncuran fauna) known from the end of XIX century. The CCF along with the La Pava Formation (LPF) constitutes the main syntectonic infill of intermontane basins in the extra-Andean NW Patagonia. The study of paleosols and terrestrial ichnofacies of both units in these basins, particularly in the Jacobacci basin (Rio Negro Province, Argentina), document the progressive environmental change since the end of the Miocene Climatic Optimum, related to the drying and cooling of southern South America. This change is recognized in the andic Mollisols and mollic Andisols bearing Coprinisphaera ichnofacies formed in subhumid grasslands or wooded-savannas (LPF), and in the xeric-vertic Andisols and andic Aridisols bearing Celliforma ichnofacies developed in semiarid woodlands or bushlands (CCF). However, a new U–Pb date of 14.38 ± 0.19 Ma (late Langhian), for the LPF at the Huahuel Niyeu valley in the Jacobacci basin, indicates that both landscapes co-existed likely following a vertical rainfall gradient (orographic precipitation). In the present work, we report the first mammals from the LPF recovered from the Huahuel Niyeu River associated with the dated strata. They include Palaeothentes intermedius, Prozaedyus sp., Proeutatus sp., Propalaehoplophorinae indet., Glossotheriopsis pascuali, Massoiamys obliquus, Pliolagostomus friasensis, Eusigmomys cf. E. oppositus, Pachyrukhos moyani, Hemihegetotherium tantillum, Protypotherium australe, Protypotherium praerutilum, Palyeidodon obtusum, Hyperoxotodon sp. nov, Toxodontidae indet., and Astrapotheriidae indet. All these taxa (except P. intermedius) also occur in roughly coeval sediments of the CCF in Jacobacci and other basins of NW Patagonia. We conclude that the heterogeneous landscape developed in Jacobacci basin was inhabited by diverse functional groups of Colloncuran mammals adapted to different climatic and floristic settings, and therefore they are not sensitive to small-scale environmental heterogeneity. These palaeoecologic inferences could be extended to other Miocene basins and to other Cenozoic mammal faunas of Patagonia, which paleohabitats were generally deduced from feeding behaviors.